The End of History in Graham Swift’s Waterland - Addouche, Nawel (My University, 2017)
This thesis aims to define the relationship between “the End of history” as philosophical concept and postmodernist critique of history in contemporary English literature notably in Graham Swift’s Waterland as historiographic metafiction, with the aim to explore the meaning of history and its end, through relying on Fukyama interpretation to the end of history, in which the research paper shows the difference between his position and postmodern attitudes. Moreover the research investigates the postmodern reaction to the notion of referring to history as Grand narrative, Furthermore the objective is to examine how the concept of the “End of History” is represented by the Grand narrative Tom Crick and how the past or history is being questioned in swift’s Waterland which allows us to get a full understanding of the nature of history itself.
Keywords: English novel; History and narrative; Graham Swift’s Waterland; Grand Narrative and historiographic metafiction; Analyse and critics